Preparing institutions for the transition: consortial cost-sharing models in transformative agreements in Austria - Rita Pinhasi; Brigitte Kromp (Insights: The UKSG Journal)
Over the past ten years, the member institutions of the Austrian Academic Library Consortium (KEMÖ) have gradually opened up their researchers’ publications to the world, one publisher at a time. By pulling their resources together, KEMÖ members have successfully converted their subscription-only agreements, for the most part, to read and publish deals in a cost-neutral manner, which include an article allocation comfortably covering the consortium’s publishing needs. However, the new business models disrupted the pre-transition status quo: the existing distribution of costs, based predominantly on institutional subscription spending, differed from the emerging institutional-level output and potential associated costs. While moving to fully article-based pricing was felt premature, the consortium decided to explore ways to make the internal cost distribution more equitable. This article presents the various cost-sharing models reviewed and the process leading to the models ultimately introduced for several transformative agreements.